Employee Welfare Review through Environmentally Friendly Behavior - Fiqriyah, Khoerunnisa; Kadiyono, Anissa Lestari; Hinduan, Zahrotur R. (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The worsening climate conditions in Indonesia has pushed numerous companies to transform themselves to become a green company that aims to preserve the environment through their daily operations. Through Social Exchange Theory, employee green behavior is found to increase employee self-satisfaction, which in turn will enhance their well-being. This research is done to examine the relationship between employee green behavior (EGB) and employee well-being (EWB) among one of green company employees. This quantitative, non-experimental research involved 104 employees from one of the green company. This research utilized the Employee Green Behavior questionnaire developed based on The Green Five Taxonomy to measure EGB, as well as the Employee Well-Being questionnaire to measure EWB. Both are self-report questionnaires. The results of this research indicate a significant positive relationship between employee green behavior (p=0.01, r=0.300) and employee well-being among employees. Additionally, the study also reveals significant differences in employee green behavior and employee well-being between gender groups. This suggests the need for more comprehensive research to further two related variables.Kondisi iklim yang kian memburuk telah direspon oleh berbagai macam perusahaan di Indonesia sebagai suatu panggilan untuk melakukan perubahan, yaitu dengan bertransformasi menjadi sebuah green company yang memang bertujuan melestarikan lingkungan melalui aktivitas operasionalnya sehari-hari. Melalui teori pertukaran sosial, perilaku ramah lingkungan ditemukan dapat meningkatkan kesejahteraan karyawan tersebut. Penelitian ini dilakukan dengan tujuan mengetahui hubungan antara employee green behavior (EGB) dan employee well-being (EWB) pada karyawan. Penelitian ini menggunakan metode penelitian kuantitatif non-eksperimental dan melibatkan 104 salah satu perusahaan yang mengusung green company. Peneliti menggunakan alat ukur Employee Green Behavior yang dikembangkan berdasarkan The Green Five Taxonomy untuk mengukur EGB, serta alat ukur Employee Well-Being untuk mengukur EWB. Kedua penelitian bersifat self-report questionnaire. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara EGB (p=0,01, r=0,300) dengan EWB pada karyawan. Penelitian ini juga menunjukkan adanya perbedaan EGB dan EWB yang signifikan antara kelompok jenis kelamin. Artinya, dibutuhkan adanya penelitian lebih komprehensif untuk melihat lebih dalam kedua variabel ini.